2011
DOI: 10.1177/0969733011408041
|View full text |Cite
|
Sign up to set email alerts
|

The ethical component of professional competence in nursing: An analysis

Abstract: The purpose of this article is to initiate a philosophical discussion about the ethical component of professional competence in nursing from the perspective of Brazilian nurses. Specifically, this article discusses professional competence in nursing practice in the Brazilian health context, based on two different conceptual frameworks. The first framework is derived from the idealistic and traditional approach while the second views professional competence through the lens of historical and dialectical materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 9 publications
1
40
0
Order By: Relevance
“…, Kälvemark Sporrong et al . , Paganini & Egry ). Responsibility of ethical competence has been seen as a duty of both nurses and nurse leaders (Heikkinen et al .…”
Section: Introductionmentioning
confidence: 96%
“…, Kälvemark Sporrong et al . , Paganini & Egry ). Responsibility of ethical competence has been seen as a duty of both nurses and nurse leaders (Heikkinen et al .…”
Section: Introductionmentioning
confidence: 96%
“…, ICN ) that enhance professional practice (Kälvemark Sporrong et al . , Paganini & Egry ). Ethical competence is a component of professional nursing competence, which is formed, in a social context through an individual development process (Jormsri et al .…”
Section: Introductionmentioning
confidence: 96%
“…, Kälvemark Sporrong et al . , Paganini & Egry ). Paganini and Egry () state that, ‘competence is a condition of performance, being the underlying mechanism which permits the integration of the many types of knowledge and acts necessary to the realization of a task'.…”
Section: Introductionmentioning
confidence: 96%
“…Studies on this topic can be identified in the scientific bases (7,11) , and many address the ethical competence in teaching (12)(13) . Few develop the theme of ethical competence in PHC, which shows the lack of production in this scenario.…”
Section: Introductionmentioning
confidence: 99%
“…The meaning of being ethically responsible is dealing with the ethical demand in a critical, reflective and resolutive manner (7) .…”
Section: Introductionmentioning
confidence: 99%